2002
DOI: 10.1007/s00018-002-8467-x
|View full text |Cite
|
Sign up to set email alerts
|

PPARs: transcriptional effectors of fatty acids and their derivatives

Abstract: Peroxisome proliferator-activated receptors (PPARs) are nuclear hormone receptors that mediate the effects of fatty acids and their derivatives at the transcriptional level. These receptors stimulate transcription after activation by their cognate ligand and binding to the promoter of target genes. In this review, we discuss how fatty acids affect PPAR functions in the cell. We first describe the structural features of the ligand binding domains of PPARs, as defined by crystallographic analyses. We then presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
198
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(210 citation statements)
references
References 82 publications
6
198
1
2
Order By: Relevance
“…The observation that binding of non-fluorescent ligands significantly quenched the emission of PPARαΔAB aromatic amino acid residues (Figs. [1][2][3][4] suggests that ligand binding altered the conformation of PPARα. To further examine whether the binding of naturally-occurring VLCFA alter PPARα structure, the effect of these ligands on the circular dichroic (CD) spectra of PPARα was examined.…”
Section: Effect Of Very-long-chain Fatty Acids On Pparα Secondary Strmentioning
confidence: 99%
“…The observation that binding of non-fluorescent ligands significantly quenched the emission of PPARαΔAB aromatic amino acid residues (Figs. [1][2][3][4] suggests that ligand binding altered the conformation of PPARα. To further examine whether the binding of naturally-occurring VLCFA alter PPARα structure, the effect of these ligands on the circular dichroic (CD) spectra of PPARα was examined.…”
Section: Effect Of Very-long-chain Fatty Acids On Pparα Secondary Strmentioning
confidence: 99%
“…28 As concerns PPARg agonists, a range of fatty acids, including the polyunsaturated fatty acids, linoleic acid and arachidonic acid, was found to bind to PPARg and regulate gene transcription. 18,29,30 In a previous study we reported that the effects of CLA on cell growth or death in prostate and bladder cancer cells seemed to involve the PPARg isoform. 13 More recently, it has been suggested that the PPARsignaling pathway is connected with the b-catenin pathway.…”
mentioning
confidence: 94%
“…16,17 PPARs are ligand-activated transcription factors that are members of the nuclear hormone receptor superfamily. 18 As other ligand-activated transcriptional factors of this superfamily, PPARs heterodimerize with 9-cis retinoic acid receptors and interact with specific DNA response elements (PPRE) located upstream of the target genes. These include genes involved in lipid metabolism and in the regulation of cell cycle and differentiation.…”
mentioning
confidence: 99%
“…The three PPAR isotypes (named ␣, ␤/␦, and ␥ or NR1C1, NR1C2, and NR1C3 (5)) are mainly involved in lipid and glucose homeostasis, regulation of food intake and body weight, and control of inflammation and wound healing (6,7). They are activated by naturally occurring or metabolized fatty acids derived from the diet or from intracellular signaling pathways and induce gene transcription as heterodimers with RXRs (8). PPARs are also very important therapeutic targets for the treatment of hyperlipidemia and type 2 diabetes.…”
mentioning
confidence: 99%